Book review: Brian Schrag and Kathleen J. Van Buren, Make Arts for a Better Life: A Guide for Working with Communities. (December 2019) - De, Mousumi
Brian Schrag and Kathleen J. Van Buren, Make Arts for a Better Life: A Guide for Working with Communities . New York, NY: Oxford University Press, 2018, 352 pp., 35. ISBN: 9780190878283 (pbk.); 9780190878276 (hardcover).